Gambaran Hasil Pemeriksaan Genexpert pada Penderita Tuberkulosis Paru dengan Komplikasi di Rumah Sakit Panti Rapih Yogyakarta - Adelia Amanda Puteri; Widaninggar Rahma Putri; Wiwit Probowati (Yayasan Literasi Sains Indonesia, 2025)
Pulmonary tuberculosis (TB) continues to pose a significant worldwide health concern, particularly when associated with complications. Delays in diagnosis and identification of drug resistance in these cases can increase morbidity and mortality. This descriptive analytical study using cross-sectional methodology aims to explain the results of GeneXpert examination, a rapid molecular diagnostic instrument, in patients with pulmonary tuberculosis with complications at Panti Rapih Hospital, Yogyakarta. In 2024, secondary data collection using a total sampling strategy, which included 660 patients with pulmonary and extrapulmonary tuberculosis, resulted in 132 cases of pulmonary tuberculosis and 32 samples that met the inclusion criteria. The findings showed that the sample was dominated by men (56.3%) of productive age (75%), with pleural effusion as the most common complication. The main GeneXpert finding was that more than half of the samples (59.4%) showed